Strategies for managing agrobiodiversity by peasant farmers in the Cerrado-Caatinga ecotone, Southwest Piauí, Brazil - Sousa, Thiago Batista; Silva, Andrea Leme da; Coutinho, Joxleide Mendes da Costa Pires (Sustainability in Debate, 2024)
The relevance of agroecological strategies for conserving agrobiodiversity in areas with rich biodiversity, such as the Cerrado-Caatinga ecotone, is not well studied. The objective of this study is to understand the uses and management of rural agroecosystems in Southwest Piauí, Brazil, focusing on the relationships between biological and cultural diversity within the context of expanding the agricultural frontiers in Matopiba. The fieldwork data were collected through semi-structured interviews with 18 informants, exploratory walks through the agroecosystems, participant observation, and photographic documentation. The key strategies for managing agrobiodiversity by peasants include safeguarding biological diversity (i.e. native seeds, and agricultural species and varieties), and the multifunctionality of managed spaces (i.e. plant harvesting and animal husbandry in the communal areas of Cerrado and Caatinga). As a result, we identified over 80 species cultivated in small-farms and home gardens within the scope of managed plants, along with high intraspecific diversity. These practices reflect a co-evolutionary relationship between peasant farmers and their environment, where diversity is essential for the climate resilience of agroecosystems and the food security of communities. The expansion of soybean monoculture represents severe threats through deforestation, loss of communal territories, and the homogenisation of cultivated species, endangering both ecological and biocultural diversity.